Managing Pain Problems in Elderly Patients with Hypertension Through Murottal Therapy - Hidayat, Taufik; Pefbrianti , Diana; Noor Ifansyah, M (CV. Inara, 2025)
The community service partner is the elderly and families in Tambak Baru Ilir Village. Hypertension in the elderly is often accompanied by pain, either due to complications of hypertension or due to physical decline due to aging. Uncontrolled pain can lead to increased blood pressure, sleep disturbances, depression, and a reduced quality of life. In addition to pharmacological treatment, non-pharmacological approaches are needed to help reduce pain, one of which is Quranic recitation therapy. Recitation therapy has been shown to have a calming effect and can help reduce anxiety and stress levels, as well as improve sleep quality in the elderly, contributing to pain reduction and blood pressure stabilization. The result of this interventions, There was a decrease in pain levels in elderly people with hypertension after being given Murottal therapy in Tambak Baru Ilir Village. Murottal therapy activities can be given to elderly people with hypertension to reduce the level of pain they feel.